Digital Library Information System at Brebes Boarding School Vocational High School - Aji Wicaksono (Journal Research of Social Science, Economics, and Management, 2021)
In the world of education, Information technology is very necessary for students and teachers to gain a broad knowledge. Students will seek additional information other than those taught by the teacher, all of which can be obtained from the library. Library is one of the facilities owned by SMK Boarding School Brebes. The library is handled by a librarian and two administrative persons. Administrative tasks vary considerably. So far, administrators process member data input, book data input, return borrowing input and make annual monthly report using computerized. But whether only with computerization that is in the library. Then what if the students want to know information about what book collections are available without having to come keperpustakaan, For that need to be designed digital library applications that can be accessed by students and teachers through the internet. In digital library information system pembutan design method used is Data Flow Diagram (DFD), with Dreamweaver CS4 application, SQL Server 2008 for database design. By using this digital library information system can facilitate information about what book collection is available without having to come keperpustakaan.